2015
DOI: 10.1586/14737140.2015.1014035
|View full text |Cite
|
Sign up to set email alerts
|

Risk of selected gastrointestinal toxicities in patients with advanced non-small cell lung cancer receiving erlotinib: a systematic review and meta-analysis

Abstract: We performed a meta-analysis of diarrhea and stomatitis associated with erlotinib use in patients with advanced non-small cell lung cancer. Eligible studies included randomized trials of patients with non-small cell lung cancer on erlotinib describing events of diarrhea and stomatitis. A total of 19 clinical trials including 7524 patients were considered eligible for the meta-analysis. The relative risk of all-grade diarrhea and stomatitis were 2.96 (95% CI: 2.31-3.8; p < 0.00001), 3.62 (95% CI: 2.43-5.39; p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Most of the meta-analyses focused on the effect of EGFR-TKIs 4 , 29 31 have been published; some studies that determined the toxicity mostly focused on the fatal AEs such as treatment-related mortality, 32 interstitial lung disease, 9 skin rash, 33 and gastrointestinal toxicities. 34 To the best of our knowledge, this is the first meta-analysis to demonstrate a significantly decreased risk of ≥grade 3 neutropenia and leukopenia as a result of erlotinb-related treatment compared with CT. Many RCTs focused on the effect of erlotinib in advanced NSCLC, 5 7 , 21 - 28 the effect including PFS, OS, objective response rate, and so on.…”
Section: Discussionmentioning
confidence: 77%
“…Most of the meta-analyses focused on the effect of EGFR-TKIs 4 , 29 31 have been published; some studies that determined the toxicity mostly focused on the fatal AEs such as treatment-related mortality, 32 interstitial lung disease, 9 skin rash, 33 and gastrointestinal toxicities. 34 To the best of our knowledge, this is the first meta-analysis to demonstrate a significantly decreased risk of ≥grade 3 neutropenia and leukopenia as a result of erlotinb-related treatment compared with CT. Many RCTs focused on the effect of erlotinib in advanced NSCLC, 5 7 , 21 - 28 the effect including PFS, OS, objective response rate, and so on.…”
Section: Discussionmentioning
confidence: 77%
“…GI toxicities have long been reported also in a number of other targeted therapeutics used in cancer management and, likewise, they have been linked to dose reduction and/or interruption [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal disorders are very common adverse events of cancer treatments including chemotherapy and targeted therapies. Erlotinib induces diarrhoea in 10·2% to 67% of patients with NSCLC, whereas rates of high‐grade diarrhoea range from 0·6% to 12·5% . A meta‐analysis found that the addition of an EGFR‐TKI to a chemotherapy significantly increased the incidence of diarrhoea .…”
Section: Details Of the Casementioning
confidence: 99%